Oral Antioxidant Vitamins and Magnesium Limit Noise-Induced Hearing Loss by Promoting Sensory Hair Cell Survival: Role of Antioxidant Enzymes and Apoptosis Genes - Juan C. Alvarado; Verónica Fuentes-Santamaría; Pedro Melgar-Rojas; María C. Gabaldón-Ull; José J. Cabanes-Sanchis; José M. Juiz (MDPI AG, 2020)
Noise induces oxidative stress in the cochlea followed by sensory cell death and hearing loss. The proof of principle that injections of antioxidant vitamins and Mg2+ prevent noise-induced hearing loss (NIHL) has been established. However, effectiveness of oral administration remains controversial and otoprotection mechanisms are unclear. Using auditory evoked potentials, quantitative PCR, and immunocytochemistry, we explored effects of oral administration of vitamins A, C, E, and Mg2+ (ACEMg) on auditory function and sensory cell survival following NIHL in rats. Oral ACEMg reduced auditory thresholds shifts after NIHL. Improved auditory function correlated with increased survival of sensory outer hair cells. In parallel, oral ACEMg modulated the expression timeline of antioxidant enzymes in the cochlea after NIHL. There was increased expression of glutathione peroxidase-1 and catalase at 1 and 10 days, respectively. Also, pro-apoptotic caspase-3 and Bax levels were diminished in ACEMg-treated rats, at 10 and 30 days, respectively, following noise overstimulation, whereas, at day 10 after noise exposure, the levels of anti-apoptotic Bcl-2, were significantly increased. Therefore, oral ACEMg improves auditory function by limiting sensory hair cell death in the auditory receptor following NIHL. Regulation of the expression of antioxidant enzymes and apoptosis-related proteins in cochlear structures is involved in such an otoprotective mechanism.